2016
DOI: 10.1108/jme-04-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning English in a multicultural classroom: strategies and opportunities

Abstract: Purpose This paper aims to explore the beliefs and experiences of a group of teachers endeavouring to enhance their students’ learning of English while adapting to a multicultural classroom reality. Design/methodology/approach The paper is based on the results of a case study involving a number of semi-structured interviews. Findings The paper illustrates how the teachers and their learners adopted a number of strategies to make the most of the opportunities of learning English within a multilingual contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Hence, English is owned by all people in the world with different social functions rather than merely owned by its native speakers. The users of English in this sense are, by nature, mult icultural (Xerri, 2016) so that at the international level, English communicat ion always takes place within an intercultural or cross -cultural dimension (Fang, 2017;López-Rocha, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, English is owned by all people in the world with different social functions rather than merely owned by its native speakers. The users of English in this sense are, by nature, mult icultural (Xerri, 2016) so that at the international level, English communicat ion always takes place within an intercultural or cross -cultural dimension (Fang, 2017;López-Rocha, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tartjwik, Brok, Veldman & Wubbles in their research [31] suggested the ideas of Evertson and Weinsten that the strategy carried out by building positive relationships through shaking hands and being friendly, class management using the social and moral curriculum, and teachers need to consider the background characteristics of students. Another thing to realize is that the development of tolerance in multicultural classes is not only centered on the teacher, but the school must encourage and participate to make it happens [32]. The explanation gives a clear deception that multicultural class is a combination of various existing systems.…”
Section: Promoting Tolerance In the Multicultural Classroomsmentioning
confidence: 99%
“…From the perspective of communication science, in particular English speaking communication which exists in intercultural communication dimension, politeness pragmatic principle was needed in order to avoid perspectives conflict in communication (Byram et al, 2002;Hua, 2013). This politeness perspective is included in the category of enhancing awareness of diversity (Xerri, 2016). Scientists concerned on examining English speaking communication, especially in the context of English language communication as world's lingua franca or international language agree that learning about politeness pragmatic is one of the steps to enhance intercultural communication competency (Badrkoohi, 2018;Byram & Wenger, 2018;Galante, 2015;Ghasemi, Ahmadian, Yazdani, & Amerian, 2020;Inkaew, 2016;Kusumaningputri & Widodo, 2018;Leggett, 2014;López-Rocha, 2016;Tran & Seepho, 2017).…”
Section: Would You Like To Join Me To Be the Moderator Of My Presentation? (Participant 15)mentioning
confidence: 99%